How Long are The Titles behind Your Name? - Ari Kamayanti (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
Riset ini mengeksplorasi bagaimana akademisi akuntansi terjebak dalam